Ferritin / albumin ratio could be a new indicator of COVID-19 disease mortality - Taşkin, Öztürk; Yilmaz, Ayşe; Soylu, Veysel Garani; Demir, Ufuk; Çatan Inan, Funda (Journal of Infection in Developing Countries, 2023)
Introduction: Despite significant advances in the management of patients with COVID-19, there is a need for markers to guide treatment and predict disease severity. In this study, we aimed to evaluate the relationship of the ferritin/albumin (FAR) ratio with disease mortality. Methodology: Acute Physiology and Chronic Health Assessment II scores and laboratory results of patients diagnosed with severe COVID-19 pneumonia were retrospectively analyzed. The patients were divided into two groups: survivors and non-survivors. Data for ferritin, albumin, and ferritin/albumin ratio among COVID-19 patients were analyzed and compared. Results: The mean age was higher in non-survivors (p = 0.778, p < 0.001, respectively). The ferritin/albumin ratio was significantly higher in the non-survival group (p < 0.05). Taking the cut-off value of the ferritin/albumin ratio of 128.71 in the ROC analysis, it predicted the critical clinical status of COVID-19 with 88.4% sensitivity and 88.4% specificity. Conclusions: ferritin/albumin ratio is a practical, inexpensive, and easily accessible test that can be used routinely. In our study, the ferritin/albumin ratio has been identified as a potential parameter in determining the mortality of critically ill COVID-19 patients treated in intensive care.
Keywords: Critical Care; Albumin; ferritin; COVID-19; Prognosis; mortality; RC31-1245; Microbiology; QR1-502; ferritin/albumin ratio; ROC Curve; Albumins; Ferritins; Humans; predictive; Internal medicine; Retrospective Studies; 3. Good health